Pediatric Bipolar Disorder - An Orphan Diagnosis - Faheem Khan; Mukesh Bhimani; Tayyab Afreen (Journal of the Dow University of Health Sciences, 2012)
"12 years old boy brought by his parents in clinic with irritability, taking great interest in games, answering in class before asked by teacher, reaching school earlier than anyone else, asking his mother to send him for Olympics and whole night watching TV, attempting to engage his teacher in a friendship. This all developed  brusquely. Parents denied any previous history of mood disorder or substance use, but on detail assessment revealed that last year he became little quiescent than usual and has left going to gym for 20 days, without any specific reason. Diagnosis was made of Bipolar affective disorder"